2008
DOI: 10.1097/mbc.0b013e328304b61a
|View full text |Cite
|
Sign up to set email alerts
|

Overfatness, stunting and physical inactivity are determinants of plasminogen activator inhibitor-1activity, fibrinogen and thrombin–antithrombin complex in African adolescents

Abstract: We examined fibrinogen, thrombin-antithrombin complex, factor VIIIc and plasminogen activator inhibitor-1 activity in African children in order to determine haemostatic profile patterning and to identify possible subdivisions at high risk for cardiovascular disease. In a cross-sectional analysis, a convenience sample of 117 girls and 78 boys (15.6 +/- 1.35 years) in a South African township was investigated within the Physical Activity in Youth study. Haemostatic variables were investigated in the total group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
1
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 51 publications
1
14
1
1
Order By: Relevance
“…It strongly affects haemostasis, blood rheology, platelet aggregation, and endothelial function [47]. The present study revealed no significant correlation between FB levels and BMI in obese subjects, in contrast to previous studies [45,50]. However, FB concentrations have been previously found to be elevated and be positively correlated with measures of total and visceral adiposity in childhood [7,45], probably secondarily, following an increase in the FB fractional synthesis rate [6].…”
Section: Discussioncontrasting
confidence: 85%
“…It strongly affects haemostasis, blood rheology, platelet aggregation, and endothelial function [47]. The present study revealed no significant correlation between FB levels and BMI in obese subjects, in contrast to previous studies [45,50]. However, FB concentrations have been previously found to be elevated and be positively correlated with measures of total and visceral adiposity in childhood [7,45], probably secondarily, following an increase in the FB fractional synthesis rate [6].…”
Section: Discussioncontrasting
confidence: 85%
“…According to the literature, there are no reports of serum adiponectin values in these children. In one study, similar concentrations of PAI-1 have been found in stunted children and non-stunted controls ( 6 ) . In another study, accelerated weight gain in children with a low birth weight or with a history of underweight in childhood has been found to be positively associated with high concentrations of PAI-1 in adulthood and an increased risk of CVD ( 7 ) .…”
supporting
confidence: 52%
“…Of the 96 studies [16][18], [20], [24]–[26], [29], [36], [39], [40], [43], [45], [46], [48], [51], [53][56], [59][61], [63][68], [70]–[72], [74], [76]–[80], [83], [85], [86], [89], [91], [92], [95], [96], [98], [103][105], [107], [109][114], [116]–[120], [123], [124], [126], [128], [129], [132], [133], [135], [136], [140], [143], [147], [149][152], [163], [169], [170], [214], [215], [218], [225], [281], [287], [289], [292], …”
Section: Resultsunclassified